A longitudinal analysis of the role of potentially morally injurious events on COVID-19-related psychosocial functioning among healthcare providers - Lauren M. Borges (Public Library of Science (PLoS), 2021)
Medical leaders have warned of the potential public health burden of a “parallel pandemic” faced by healthcare workers during the COVID-19 pandemic. These individuals may have experienced scenarios in which their moral code was violated resulting in potentially morally injurious events (PMIEs). In the present study, hierarchical linear modeling was utilized to examine the role of PMIEs on COVID-19 pandemic-related difficulties in psychosocial functioning among 211 healthcare providers (83% female, 89% White, and an average of 11.30 years in their healthcare profession [9.31]) over a 10-month span (May 2020 –March 2021). Reported exposure to PMIEs was associated with statistically significant poorer self-reported psychosocial functioning at baseline and over the course of 10-months of data collection. Within exploratory examinations of PMIE type, perceptions of transgressions by self or others (e.g., “I acted in ways that violated my own moral code or values”), but not perceived betrayal (e.g., “I feel betrayed by leaders who I once trusted”), was associated with poorer COVID-19 related psychosocial functioning (e.g., feeling connected to others, relationship with spouse or partner). Findings from this study speak to the importance of investing in intervention and prevention efforts to mitigate the consequences of exposure to PMIEs among healthcare providers. Interventions for healthcare providers targeting psychosocial functioning in the context of moral injury is an important area for future research.